Job Stress and Employee Mental Health during Economic Recession: Evidence from Nigeria’s Oil and Gas Sector - Oginni, Babalola Oluwayemi; Ayantunji, Isola O.; Larnre-Babalola, Folakemi O.; Ajibola, Kolawole S.; Balogun, Ramat A.; Ogunlusi, Christopher Femi (Acta Universitatis Danubius. Œconomica, 2023)
The study was carried out using the economic recession as the propelling factor to determine the job stress level and employee mental health status and examine their relationship using the Oil and Gas industries in the Central Senatorial District of Lagos as the unit of analysis. The study made use of multi-stage sampling techniques to select the sample, sample size, and the administration of the questionnaire to capture and preserve the characteristics of the respondents. From the analysis of data collected, it was found that the level of job stress was very high based on the variable indices such as qualification, co-workers’ relationship and human relations, poor administrative and technical support, terms and conditions of employment, workload and time pressure, adequacy of compensation packages, family and work life relations, and superior-subordinate relationship, as well as the organizational policies and these indices, independently and significantly influenced employee mental health negatively at 0.05 level of Sig. it was concluded that economic recession as experienced by the sector was responsible for the high level of stress among the employees which invariably affect the mental health of employees to be poor/low. It was recommended that the management of these organizations should endeavour to improve the existing organizational policies to reduce friction and improve mental health.